Synthesis and characterization of sulphated AIMCM-41 and its catalytic activity in dibenzoylation of biphenyl with benzoyl chloride - Ng, Eng Poh (2006)
Benzoylation of biphenyl with benzoyl chloride is an important acylation reaction, producing monosubstituted product, 4-phenyl benzophenone (4-PBP) and disubstituted product, 4, 4’- dibenzoylbiphenyl (4, 4’-DBBP). 4, 4’-DBBP is a monomer used as a component in emitting layer in polymer light emitting (PLED) devices. The objective of this study is to synthesize and characterize a highly active sulphated AlMCM-41 acid catalyst by enhancing its acidity through sulphation. Firstly, the AlMCM-41 with various SiO2/Al2O3 ratios was prepared by direct synthesis, followed by conversion to H-AlMCM-41 via ion exchange of NaAlMCM-41 with ammonium nitrate. Finally, sulphated AlMCM-41 was prepared by impregnation of sulphuric acid in toluene. The sulphated MCM-41 materials possess high surface area (>500 m2/g) and large quantities of Brönsted acid sites after characterizing with surface analyzer and pyridine infrared spectroscopy. 27Al MAS NMR indicates the presence of octahedrally coordinated extra-framework sulphated aluminiums (EFAL) and aluminium sulphate. The Hammett indicators show that the acid strength of the sulphated AlMCM-41 materials was stronger than sulphuric acid and H-AlMCM-41 because of sulphate groups attached to aluminium atom in sulphated AlMCM-41. The results of comparative study on the dibenzoylation of biphenyl reaction indicate that only sulphated AlMCM-41 gives both monosubstituted 4-PBP and disubstituted 4, 4’-DBBP with the highest activity compared to sulphuric acid, H-AlMCM-41 and sulphated amorphous silica.